Effect of Job Satisfaction and Compensation Organizational Commitment to Performance Teacher at SMP Negeri 2 Sibolga - Kalaudia Maranata Simanjuntak; Amini Amini; Indra Prasetia (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to analyze the effect of: Job Satisfaction on Teacher Performance at SMP Negeri 2 Sibolga, Compensation on Teacher Performance at SMP Negeri 2 Sibolga, Organizational Commitment to Teacher Performance at SMP Negeri 2 Sibolga, Job Satisfaction, Compensation, Organizational Commitment to Teacher Performance at SMP Negeri 2 Sibolga. The population in this study were all teachers in Sibolga 2 Public Junior High School, totaling 46 people. Methods of data collection using a questionnaire. Then tested the validity and reliability. The data analysis technique used is multiple linear regression, hypothesis testing, and the coefficient of determination. The results of the study show that: (a) The relationship between the variable Job Satisfaction (X1) and teacher performance (Y) is in the form of a regression equation Y = 25.513 + 0.323 X1. This means that if Job Satisfaction increases by 1 point then the teacher's performance will increase by 0.323 points at a constant of 25.513 then Ha is accepted and Ho is rejected. (b) The relationship between the compensation variable (X2) and teacher performance (Y) is in the form of a regression equation Y = 23.332 + 0.473 X1. This means that if the compensation increases by 1 point, the teacher's performance will increase by 0.473 points at a constant of 23.332. Then Ha is accepted and Ho is rejected. (c) The relationship between the Organizational Commitment variable (X3) and teacher performance (Y) is in the form of a regression equation Y = 24.150 + 0.434X1. This means that if compensation increases by 1 point, the teacher's performance will increase by 0.434 points at a constant of 24.150. Then Ha is accepted and Ho is rejected. (d) Because Fcount > Ftable or 11,699 > 2,827, Ha is accepted and Ho is rejected so it can be written that there is an influence of Job Satisfaction, Compensation and Organizational Commitment together on the performance of SMP Negeri 2 Sibolga teachers.